Varying sun protection of young children by migrant and Australian‐born mothers - Fay Scheltinga; Rania Shibl; Adele C. Green; Shu‐Kay Ng; Paul A. Scuffham; Cate M. Cameron (Elsevier, 2014)
Abstract Objective: To compare sun protection by Australian‐born and migrant mothers of three‐year‐old children. Methods: Australian‐born and migrant mothers taking part in the Environments for Healthy Living prospective birth‐cohort study were asked standard questions about their child's sun protection. Children were given a skin cancer susceptibility score based on grandparents' ethnic origin. Logistic regression was used to estimate odds ratios (ORs) to measure the association of sun protection of children according to mothers' migrant status adjusted for socio‐demographic characteristics. Results: A total of 613 Australian‐born and 224 migrant mothers of three‐year‐old children were studied. Mothers who had migrated less than four years ago were more likely to allow their three‐year‐old to spend more than two hours outdoors between 10 am and 3 pm compared to Australian‐born mothers (OR=2.80, 95%CI 1.20-6.57). Mothers from high latitude countries (>45 degrees) were more likely to apply sunscreen to their child than those from lower latitude countries (OR=3.15, 95%CI 1.03-9.61). Conclusions and implications: Strategies should aim to increase general awareness about the need for sun protection of young children, and recent migrants should be alerted to the harms of excessive sun exposure.